2022
DOI: 10.1097/md.0000000000030628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical, biochemical, and radiological outcomes following intra-articular injection of Wharton jelly-derived mesenchymal stromal cells in patients with knee osteoarthritis: A prospective clinical study

Abstract: The aim of the present study was to perform clinical, biochemical, and radiological evaluation of the efficacy of mesenchymal stem cells derived from Wharton jelly (WJ) present within the human umbilical cord in the treatment of knee osteoarthritis. Between 2018 and 2019, 10 patients with knee osteoarthritis for whom the conservative treatment was not beneficial were included in the study. Patients were clinically, radiologically, and biochemically evaluated before treatment initiation. Thereafter, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Among them, MSCs are considered as a kind of alternative seed cells to treat OA because of their extensive sources, easy access, great potential for self-proliferation and multi-differentiation, and ability to regulate inflammation ( Barry and Murphy, 2013 ; Bertoni et al, 2021 ; Hwang et al, 2021 ). Numerous previous clinical studies have systematically demonstrated that intra-articular injection of MSCs can improve cartilage damage and relieve pain in patients with OA ( Aletto et al, 2022 ; Carvalho Schweich-Adami et al, 2022 ; Gunay et al, 2022 ). Specifically, ADSCs significantly reduced OA cartilage damage in rats, which can be achieved by down-regulating MMP-13 and COL-X and up-regulating COL-2.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, MSCs are considered as a kind of alternative seed cells to treat OA because of their extensive sources, easy access, great potential for self-proliferation and multi-differentiation, and ability to regulate inflammation ( Barry and Murphy, 2013 ; Bertoni et al, 2021 ; Hwang et al, 2021 ). Numerous previous clinical studies have systematically demonstrated that intra-articular injection of MSCs can improve cartilage damage and relieve pain in patients with OA ( Aletto et al, 2022 ; Carvalho Schweich-Adami et al, 2022 ; Gunay et al, 2022 ). Specifically, ADSCs significantly reduced OA cartilage damage in rats, which can be achieved by down-regulating MMP-13 and COL-X and up-regulating COL-2.…”
Section: Resultsmentioning
confidence: 99%
“…Included in the 50 studies were 16 RCTs [ 42 57 ], 10 controlled trials [ 58 67 ], and 24 single-arm studies [ 68 91 ]. There were 1223 patients, including 565 men and 807 women (sexes ratio was missed in four studies).…”
Section: Resultsmentioning
confidence: 99%
“…The study was limited by its small sample size, short follow-up period, absence of a control group and lack of histopathological analysis, suggesting the need for further research with larger patient cohorts, histopathological analyses, extended observation periods and comparison to control groups. 44 …”
Section: Resultsmentioning
confidence: 99%